Pompe disease - What do we currently know about the disease? - Białowąs, Edyta; Mazurek, Magdalena; Aghadi, Artur; Cuber, Iwona; Dybała, Ewelina; Szela, Karolina (Journal of Education, Health and Sport, 2023)
Introduction: Pompe disease (PD) is a rare metabolic disorder caused by a partial or complete deficiency of acid α-glucosidase (GAA) which leads to lysosomal accumulation of glycogen. Excessive amounts of glycogen accumulate mainly in the cells of the heart and skeletal muscles and cause dysfunction of these tissues. It is inherited in an autosomal recessive manner. The most common diagnostic methods include genetic tests and the measurement of enzyme activity in leukocytes or fibroblasts. A screening test is also available that tests the enzyme activity in dried blood spot (DBS). The treatment of PD is mostly based on synthetic GAA enzyme supply to the patients. The therapy reduces glycogen storage and improves muscle function, decreases heart size and prolongs the lives of those with infantile form of PD. In the adult onset of the disease treatment increases physical efficiency and reduces the progression of respiratory failure. Aim of the study: Systematization of current knowledge about Pompe disease with particular emphasis on possible clinical presentations, diagnostics and therapeutic options. Material and methods: Literature review based on PubMed data using the following keywords: Pompe disease, Glycogenosis type ii, glucosidase alpha Summary : Pompe disease is a rare disease with many problems related to diagnosis and possible therapies. Its symptoms can be very misleading and cause a delay in diagnosis . It is critical to start the therapy as soon as possible to best manage the disease. The prognosis of PD is poor, especially in children under 12 months of age. Gene therapy research is currently underway and early results are very promising. There is still much to learn about dealing with this disease.